Peningkatan Hasil Belajar Peserta Didik pada Muatan IPA Melalui Metode Inquiry di Kelas VI SDN 155/X Kuala Dendang Semester Ganjil Tahun Ajaran 2021/2022 - Agus Farichin (Departement of Mathematics Education, 2022)
This study aims to describe and obtain information on improving science content learning outcomes through the Inquiry method. This research is a classroom action research which consists of two cycles, each cycle consists of two meetings. Each meeting consists of four stages, namely planning, implementation, observation and reflection. The subjects of this study were students of class VI SDN 155/X Kuala Dendang, totaling 8 people. This research was conducted in the odd semester of the 2021/2022 academic year. Data collection techniques using tests, observations, and documentation. Data were analyzed using percentages. The results showed that through the Inquiry method, it was possible to improve the learning outcomes of the sixth grade students of SDN 155/X Kuala Dendang science content.